Tindak Tutur Direktif Dalam Novel Sepasang Yang Melawan Karya Jazuli Imam (Kajian Pragmatik) - Ila Utami; Ahmad Afandi; Irwan Siagian (Departement of Mathematics Education, 2023)
The objective of this study is to describe directive speech acts in Jazuli Imam novel Sepasang Yang Melawan. The method used in this research is descriptive method with a qualitative. Data collection techniques using observation and recording. The data in this study are words, phrases, and sentences that contain directive speech acts in Jazuli Imam novel Sepasang Yang Melawan. The data source in this research is Jazuli Imam novel Sepayang Yang Melawan. The technique of checking the validity of the data uses credibility test. Data analysis techniques using content analysis techniques. The results of the study were found the existence of directive speech acts includes elements of the words forcing, inviting, asking, ordering, charging, urging, begging, suggesting, ordering, ordering and opposing.